Frequency and Association of Dyslipidemia with Clinical and Biochemical Parameters among Patients with Non-alcoholic Fatty Liver Disease: Dyslipidemia with Clinical and Biochemical Parameters among Patients with NAFLD - Ahmad, Arslan; Siddique, Shazia; Bhalli, Amanullah; Umer, Amina; Asad, Umayma; Jamil, Muhammad Irfan (Pakistan Journal of Health Sciences, 2025)
Non-alcoholic fatty liver disease (NAFLD) is increasingly associated with metabolic disorders, particularly dyslipidemia, which contributes to cardiovascular risk and disease progression. Understanding this relationship is essential for early intervention. Objectives: To assess the frequency of dyslipidemia and its association with clinical and biochemical parameters in NAFLD patients. Methods: A cross-sectional study was carried out at the Department of Medicine, Jinnah Hospital, Lahore, from November 2024 to April 2025. A total of 116 ultrasonographically confirmed NAFLD patients aged 18–70 years were registered using non-probability consecutive sampling. Patients with secondary causes of liver disease, lipid-altering medications, or systemic illnesses were excluded. Results: Among the 116 NAFLD participants, the average age was 48.67 ± 11.57 years, and the mean body mass index (BMI) was 28.27 ± 4.60 kg/m². Dyslipidemia was present in 72 (62.1%) of participants. Females comprised 44 (61.1%) of the dyslipidemic group, and 44 (61.1%) were aged 46–70 years. Diabetes mellitus and ischemic heart disease were significantly associated with dyslipidemia (p=0.016 and p=0.004, respectively). Biochemical markers, including BMI (p=0.002), AST (p=0.012), and ALT (p=0.041), were significantly elevated in dyslipidemic patients. Lipid profile abnormalities, such as total cholesterol, triglycerides, and LDL-C, were significantly higher, while HDL-C was lower (all p<0.001). Dyslipidemia prevalence increased with NAFLD severity grade (p<0.001). Conclusion: Dyslipidemia is prevalent in NAFLD and significantly correlates with disease severity and metabolic comorbidities, highlighting the need for integrated lipid and hepatic assessment in clinical management.